Pengembangan Asesmen Formatif Berbasis SLOA Pada Materi Statistika Kelas XI SMA - Adi, Faizza Zhara Adellia; Pasani, Chairil Faif; Noorbaiti, Rahmita (JURNAL PENDIDIKAN, 2026)
Formative assessment practices in classrooms still focus on final outcomes and have not optimally encouraged students’ learning reflection. This study aimed to develop a valid, practical, and effective SLOA-based formative assessment on statistics of measures of central tendency for single data. The study employed the 4-D development model without the disseminate stage. The trial subjects consisted of 26 students of class XI-12 at SMAN 7 Banjarmasin. The developed product comprised four formative assessment packages in the form of essay questions equipped with self-assessment sheets as an implementation of the Assessment as Learning (AaL) component within the SLOA framework, scoring rubrics, and answer keys. Data were collected through validation sheets, a teacher practicality questionnaire, and students’ formative assessment results. The results showed that the assessment was categorized as very valid with average scores of 3.57 and 3.75, very practical with 88%, and effective with an average completeness percentage of 88%.